Madrasah Education in India: A Need for Reformation - Wani, Hilal Ahmad (ATIKAN, 2012)
ABSTRACT: Since time immemorial, the Muslim youth who obtained Madrasah education are in doldrums in a modern world. Itâs accepted phenomenon that Madrasah had played a vital role in preaching the gospels of the great faith Islam. In the meanwhile, they dodged to keep their level with the modern education due to certain vincible hitches. At the threshold of the Islamic education, Muslim youth of Madrasahs are unable to have modern education because of which they become peregrinators. In addition, Madrasah people are following the age old syllabi, whereas they abstain themselves to opt for modern syllabi. Moreover, itâs a right time for the learned Muslims to ferret out the loopholes and pitfalls in the Madrasah education system whereby reformation and rejuvenation could be done. In order to bolster the Muslim youth to go for modern education, Madrasah people have to jettison the prejudices towards modern education and reckon the scientific education with the Islamic education. The assessment and assertion of this study is that Muslims should come forward to juxtapose Islamic education with modern education. KEY WORD: Madrasah education, modern education, Muslim society, India nation-state, and reform in education.IKHTISAR: Sudah sejak lama, para pemuda Muslim yang mendapatkan pendidikan Madrasah menjadi lesu di dunia modern. Adalah fenomena yang tak terbantahkan bahwa Madrasah memainkan peran yang sangat penting dalam mengajarkan keyakinan Islam. Sementara itu, mereka mengelak untuk mempertahankan level mereka dengan pendidikan modern dikarenakan rintangan tertentu. Pada awal pendidikan Islam, para pemuda Muslim dari Madrasah ini tidak mampu memiliki pendidikan modern dikarenakan mereka merupakan para musafir. Selain itu, orang-orang dari Madrasah ini mengikuti silabus lama, sementara mereka tidak mau memilih silabus modern. Maka, inilah waktu yang tepat bagi para Muslim yang belajar untuk menemukan jalan keluar dan perangkap dalam sistem pendidikan Madrasah dimana pembaharuan dan peremajaan dapat dilakukan. Untuk mendukung para pemuda Muslim melalui pendidikan modern, orang-orang Madrasah ini harus melepaskan prasangka terhadap pendidikan modern dan menggabungkan pendidikan ilmiah dengan pendidikan Islam. Penilaian dan penegasan dalam studi ini adalah bahwa Muslim harus maju untuk mensejajarkan pendidikan Islam dengan pendidikan modern.Â KATA KUNCI: Pendidikan madrasah, pendidikan modern, masyarakat Muslim, negara India, dan pembaharuan dalam pendidikan.About the Author: Dr. Hilal Ahmad Wani is a Post Doctoral Fellow at the Centre for Peace and Strategic Studies UOI (University of Ilorin) in Nigeria. For academic purposes, he can be contacted via his e-mail at: wanihilal@gmail.comHow to cite this article? Wani, Hilal Ahmad. (2012). âMadrasah Education in India: A Need for Reformationâ in ATIKAN: Jurnal Kajian Pendidikan, Vol.2(2) Desember, pp.235-252. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung and FKIP UNSUR in Cianjur, West Java, ISSN 2088-1290. Chronicle of the article: Accepted (October 25, 2012); Revised (November 27, 2012); and Published (December 15, 2012).